Neonatal 6-OHDA lesion model in mouse induces Attention-Deficit/ Hyperactivity Disorder (ADHD)-like behaviour. Issue 1 (December 2018) - Bouchatta, Otmane; Manouze, Houria; Bouali-benazzouz, Rabia; Kerekes, Nóra; Ba-M'hamed, Saadia; Fossat, Pascal; Landry, Marc; Bennis, Mohamed
Abstract Attention-deficit/hyperactivity disorder (ADHD) is a common neurodevelopmental disorder characterized by impaired attention, impulsivity and hyperactivity. The "neonatal 6-hydroxydopamine" (6-OHDA) lesion is a commonly used model of ADHD in rat. However, a comprehensive assessment of ADHD‐like symptoms is still missing, and data in mouse remain largely unavailable. Our aim was to analyse symptoms of ADHD in the mouse neonatal 6‐OHDA model. 6‐OHDA mice exhibited the major ADHD‐like symptoms, i.e. hyperactivity (open field), attention deficit and impulsivity (five‐choice serial reaction time task). Further, the model revealed discrete co‐existing symptoms, i.e. anxiety‐like (elevated plus maze test) and antisocial (social interaction) behaviours and decreased cognitive functioning (novel object recognition). The efficacy of methylphenidate, a classical psychostimulant used in the treatment of ADHD, was also evaluated. A histological analysis further supports the model validity by indicating dopamine depletion, changes in cortical thickness and abnormalities in anterior cingulate cortex neurons. A principal component analysis of the behaviour profile confirms that the 6‐OHDA mouse model displayed good face and predictive validity. We conclude that neonatal dopamine depletion results in behavioural and morphological changes similar to those seen in patients and therefore could be used as a model for studying ADHD pathophysiological mechanisms and identifying therapeutic targets.